1981
DOI: 10.1161/01.res.48.6.813
|View full text |Cite
|
Sign up to set email alerts
|

Volume loading slows left ventricular isovolumic relaxation rate. Evidence of load-dependent relaxation in the intact dog heart.

Abstract: SUMMARY We studied the effects of volume loading on left ventricular isovolumic relaxation rate in 16 intact anesthetized dogs. End-diastolic pressure, mean aortic systolic pressure, dp/dt mnx , and heart rate were measured at end expiration and end inspiration. Volume loading to approximately 5, 10, 15, and 20 mm Hg above initial end-diastolic pressure was performed. In nine dogs, simultaneous ventricular dimensions were measured with previously implanted tantalum screws using biplane cineangiography. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
134
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(141 citation statements)
references
References 43 publications
5
134
2
Order By: Relevance
“…13 Because it has been suggested that this relationship may not be monoexponential, we also calculated the time constraint, T d , using the method proposed by Raff and Glantz. 14 The correlation coefficients for all time constant calculations exceeded -0.90.…”
Section: Discussionmentioning
confidence: 86%
“…13 Because it has been suggested that this relationship may not be monoexponential, we also calculated the time constraint, T d , using the method proposed by Raff and Glantz. 14 The correlation coefficients for all time constant calculations exceeded -0.90.…”
Section: Discussionmentioning
confidence: 86%
“…26) dP/dt min was first defined as the starting point of the relaxation pressure curve for monoexponential fitting, 14) and subsequently monoexponential fitting from the start of dP/dt min has been used widely. 16,17,27) However, it is evident that there is a considerable gap between the best-fit monoexponential curve and the actual relaxation curve near dP/dt min . 18) Similarly, the maximum rate of decline (ie, the minimum time-derivative of force (dF/dt min )) has been used as the onset of relaxation, 28) however, other starting points for relaxation have ] i decline have been used.…”
mentioning
confidence: 99%
“…In human cardiovascular medicine, IVRT has been used for noninvasive assessment of diastolic function [22,28,29]. However, many reports have indicated that IVRT is also influenced by age, sex, preload, afterload and HR [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, many reports have indicated that IVRT is also influenced by age, sex, preload, afterload and HR [18,25]. In past reports, good correlations between left ventricular filling pressure (almost the same as mean LAP), IVRT and its modified parameters (ratio of peak E wave to IVRT) were indicated without any consideration to the stability of R-R interval under general anesthesia [22,29]. In this present study, it was very difficult to calculate IVRT in telemetrized dogs due to the instability of the R-R interval resulting from respiratory arrhythmia, and the r values were negative in 7 out of 37 cases.…”
Section: Discussionmentioning
confidence: 99%